Evaluación técnico-financiera para la producción de goma termoplástica para suelas de calzado (2017)
This document presents the parameters required to produce a thermoplastic rubber for use in shoe soles, taking into account the mechanical properties that meet the specifications of the service, through the correct selection of raw materials, seeking the best cost of these, along with The proper operating conditions to obtain the finished product. Finalizing with a financial analysis in which the viability and the return of the investment in the long term are evaluated.